ICT Adoption Framework in Rural Secondary Schools: Case of Meru, Kenya - Gatwiri, Bundi Dorothy (Strathmore University, 2013)
Secondary school teachers and administrators are under increasing pressure to use Information and Communication Technology to impart to students the knowledge, skills and attitudes they need to survive in the twenty first century. Secondary schools need to migrate from a teacher-centered lecture based instruction, to a student–centered interactive learning environment. To attain this aspiration, an ICT enabled Secondary school education is fundamental. The main goal is to understand how embedded use of ICT in a learning environment can improve the learner outcome. Towards this end, international and national authorities have been spending huge sums of money to facilitate the implementation of ICT in Secondary education. This is why the Kenyan government is encouraging ―…the use of ICT in schools, colleges, universities and other educational institutions in the country so as to improve the quality of teaching and learning.‖ With the Kenyan National ICT Policy in place, ICT continues to advance in Kenya. Rural areas still experience a lag in its implementation that continues to widen the digital and knowledge divides. This is as a result of lack of systematic guidelines that can be used for ICT adoption in the learning processes. With this premise the researcher embarked on a study based on the secondary schools in Kenyan rural areas, in Imenti North District, Meru County. The study revealed that, though the key players in the secondary school education system have the will to embrace modern methods of instruction and knowledge management, Information Communication Technology is being used merely for routine basic processes such as word processing and therefore missing out on its true potential value. Since most of the teachers are just certificate holders and others have no formal computer education. The study used both descriptive survey and case study, where a single rural area in Kenya was chosen and structured questions were provided to the respondents to guide them in areas of interest concerning ICT adoption in secondary schools. The framework is structured into five dimensions. Students‘ aspects, learning environments, Teacher professional ICT attributes, School ICT capacity and School Environments are discussed. Fundamental aspects of the ICT pedagogy are covered in the study. Finally, the relationships between all dimensions are explored and their components are discussed. This study has documented the progress made in secondary educational development, while it is applicable to other secondary schools with similar challenges and status in Kenya. The study has revealed the role of ICT in enhancing secondary education in Kenyan rural areas. The results of the study are a framework that can be used for adoption of ICTs in rural secondary schools. This framework was validated at Ntugi Day Secondary School, a public day secondary school within Imenti North District, Meru County in Kenya.
Thesis submitted in partial fulfillment of the requirements of the degree of Master of Science in Information Technology (MSc. IT)
Keywords: ICT; Rural secondary schools; Meru; Kenya